2020
DOI: 10.1038/s41598-020-69411-2
|View full text |Cite
|
Sign up to set email alerts
|

Entropy generation in MHD Casson fluid flow with variable heat conductance and thermal conductivity over non-linear bi-directional stretching surface

Abstract: This consideration highlights the belongings of momentum, entropy generation, species and thermal dissemination on boundary layer flow (BLF) of Casson liquid over a linearly elongating surface considering radiation and Joule heating effects significant. Transportation of thermal and species are offered by using the temperature-dependent models of thermal conductivity and mass diffusion coefficient. Arising problem appear in the form of nonlinear partial differential equations (NPDEs) against the conservation l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…Swain et al [32] used an exponentially porous surface to analyze the flow and thermal characterizations considering nanoparticles via slip conditions. Some recent contributions covering numerous physical aspects and computational approaches have been reported in [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Swain et al [32] used an exponentially porous surface to analyze the flow and thermal characterizations considering nanoparticles via slip conditions. Some recent contributions covering numerous physical aspects and computational approaches have been reported in [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…For the estimated modeling problem, the initial guesses are their respective linear operators fAξ=11eξ,θAξ=1eξ,ϕAξ=1eξ, LA=D3Df,LB=D21θ,LC=D21ϕ,these linear operators conform the following features LA][J1+|J2eξ+J3eξ=0, LB[J4eξ+J5eξ]=0, LC[J6eξ+J7eξ]=0,where Jnn=1,,7 are the constants which are computed by fetching the declared constraints. Averaged squared residuals as recommended in References [33‐38] for velocity, thermal and solutal fields with controlling parameters f,θ, and ϕ, are described as true…”
Section: Optimal Homotopy Analysis Methodsmentioning
confidence: 99%
“…are the constants which are computed by fetching the declared constraints. Averaged squared residuals as recommended in References [33][34][35][36][37][38] for velocity, thermal and solutal fields with controlling parameters ℏ ℏ , f θ , and ℏ , ϕ are described as…”
Section: Optimal Homotopy Analysis Methodsmentioning
confidence: 99%
“…They found that higher values of the Weissenberg parameter retard the velocity profile. Sohail et al 6 investigated the mechanism of entropy in the Casson model under variable properties. They addressed the analytical solution of the developed problem.…”
Section: Introductionmentioning
confidence: 99%